A Tenure Choice Look at the Portuguese Housing Market in the Eighties - Baleiras, Rui (2019)
A critical survey of the Portuguese housing market in the eighties is attempted in this paper, through the analysis of playing demand and supply tenure choice determinants. Some suitable policy recommendations are formulated; their effective implementation will not require a significant change on the degree of public intervention in the housing market, which has traditionally been low in Portugal when judged by European standards.